HOW DO YOU DRIVE? ANALYZING VEHICLE SENSORDATA IN PRODUCT LIFECYCLE MANAGEMENT SYSTEMS - Brandt, N.; Ahlemann, F. (Proceedings of the 28th European Conference on Information Systems (ECIS), 2020)
For most car and truck manufacturers access to information about the status of produced vehicles end with their sale. With embedded connectivity units this changes so that manufacturers can gather data from vehicle in-build sensors and thus, gain insights into each products usage. Our study investigates why manufacturers aim to integrate connectivity units into their products to gather sensor based usage information and what hinders them to do so. Thereby, we aim to identify the factors that have an influence on the decision of vehicle manufacturers to adopt the concept of the vehicle digital twin. To unveil those factors, we conducted 30 expert interviews at two vehicle manufacturers in which we found benefits and barriers regarding the realization of a product digital twin. By conceptualizing the benefits and barriers, which have a positive or negative influence on the adoption decision from the perspective of the manufacturers, we were able to derive general influences on the adoption decision. In our adapted technology-organization-environment framework we found influences in the technological (i.e. product data and product heterogeneity), the organizational (i.e. business model orientation, readiness of internal processes and digital culture) and the environmental (i.e. competitors behaviour, legal regulations and customer demand) dimension.